Social functions of synagogue song : a Durkheimian approach - Friedmann, Jonathan L., 1980- (Lexington Books, 2012)
Social Functions of Synagogue Song: A Durkheimian Approach by Jonathan L. Friedmann paints a detailed picture of the important role sacred music plays in Jewish religious communities. Drawing upon the work of Émile Durkeim, the book examines how synagogue songs serve disciplinary, cohesive, revitalizing, and euphoric functions.